Local government intervention and energy utilization efficiency: evidence from China’s NEDC policy - Wu, Saijun; Jiang, Tianhong; Hong, Min (Frontiers in Environmental Science, 2024)
Improving energy utilization efficiency is an essential way to save energy and reduce emissions. This article collects data from 3,164 samples in China and uses the SBM-DEA method to calculate energy utilization efficiency. Then, we construct the DID model based on China’s New-Energy-Demonstration-City (NEDC) policy to test the impacts of local government intervention on energy utilization efficiency (EUE). The following conclusions can be drawn. Firstly, the NEDC policy can still significantly improve EUE. Secondly, heterogeneity analysis shows that the NEDC policy is beneficial for enhancing urban EUE, whether for traditional industrial bases or non-traditional industrial bases. The impact on non-traditional industrial bases is greater. The NEDC policy can significantly promote EUE in the eastern cities and high economic development areas. In contrast, its impact on EUE in the central and western cities or low economic development areas is insignificant. Finally, mechanism analysis shows that NEDC policy can promote energy utilization efficiency through industrial structure adjustment and green innovation.